2009
DOI: 10.1055/s-0028-1128124
|View full text |Cite
|
Sign up to set email alerts
|

Extrapulmonary Tuberculosis: A Study Comparing Diabetic and Nondiabetic Patients

Abstract: This is the first study about the impacts of diabetes on EPTB. The prevalence of hypertension and chronic liver diseases, the incidence of tuberculous peritonitis, and the total bilirubin level were higher in EPTB patients with diabetes than those without diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“…India is experiencing a double epidemic of DM and HIV, both of which are strongly associated with immuno-suppression. Though HIV/TB co-infection is a known problem and HIV is considered to be the most important risk factor in the progression of TB infection to disease, DM cannot be ignored as various earlier studies have associated DM with development of TB disease [5,[7][8][9][10][11][12]. This study has retrospectively looked into the role of HIV and DM as risk factors in the TB patients (pulmonary and extra-pulmonary) of rural south India.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…India is experiencing a double epidemic of DM and HIV, both of which are strongly associated with immuno-suppression. Though HIV/TB co-infection is a known problem and HIV is considered to be the most important risk factor in the progression of TB infection to disease, DM cannot be ignored as various earlier studies have associated DM with development of TB disease [5,[7][8][9][10][11][12]. This study has retrospectively looked into the role of HIV and DM as risk factors in the TB patients (pulmonary and extra-pulmonary) of rural south India.…”
Section: Discussionmentioning
confidence: 99%
“…Several retrospective and prospective studies have associated DM with an increased risk for active TB [7][8][9][10][11][12]. While DM has been mostly associated with pulmonary TB, extrapulmonary TB has been mostly indicated in HIV infection [4,7,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In one Taiwanese study, the incidence of PTB in diabetics was as high as 26.7%, as opposed to 6.7% in nondiabetics 29. The reason for an increased risk of PTB in diabetics is believed to involve reduced phagocytic capability of peritoneal macrophages 30. Studies involving a murine model showed that among those infected with TB, diabetic mice, when compared to their non-diabetic peers, had significantly higher bacillary loads in the abdominal cavity.…”
Section: Pathologic States: Liver Cirrhosis Diabetes Mellitus and Rmentioning
confidence: 99%
“…The literature search returned six cross-sectional studies that contained data on the prevalence of hypertension among TB patients. [25][26][27][28][29][30] The majority aimed to study the burden and clinical profile of diabetes in TB patients, and the number of TB patients included varied from 75 to 38 881. The studies were conducted in Nigeria, Taiwan, Brazil, and South Africa between 2009 and 2016, and all included both sexes.…”
Section: Prevalence Of Hypertension Among Tb Patients-cross-sectionalmentioning
confidence: 99%